The Role of Intercropping Wheat with Legumes (Chickpea or Pea) in Improving the yield and Land Equivalent Ratio in Rain fed Regions - Tawfiq, Sherwan Ismael; Ahmad, Kazhala Rashed (Sulaimani Journal for Pure and Applied Sciences, 2014)
This study was conducted to estimate the response of some characters of such as biological yield, grain yield, harvest index and Land equivalent ratio. chlorophyll and protein content of Araz bread which, intercropped with two legume crops, chickpea and pea with some different patterns namely [sole wheat, sole wheat + fertilizer, 1 wheat: 1 legume (chickpea or pea) , 2 wheat: 1 legume (chickpea or pea), 1 wheat: 2 legumes(chickpea or pea) and broadcast treatments]. This experiment was conducted at two different locations Qlyasan and Kanipanka during the winter season 2008 – 2009, and was designed according to Split Plot Design within factorial experiment with three replications. As the average of both locations, the response of wheat characters to both legume crops was significant for biological yield, grain yield and harvest index. Chickpea had more effect on wheat characters than pea in biological yield, grain yield, and harvest index. The intercropping systems significantly affected the wheat characters, biological yield, grain yield, harvest index, LER, flag leaf area, chlorophyll and protein content. It was found that the cropping system of 1wheat: 2 legumes ( pea , chickpea) were more effective on most important wheat characters compared to other systems, whereas the systems of sole wheat and broadcast exhibited the lowest effect on most characters. The effect of locations was significant on most important characters and the Qlyasan location was superior in grain yield only.
Keywords: bread wheat; chickpea and pea; intercropping system; Land Equivalent Ratio